2022
DOI: 10.6018/eglobal.492291
|View full text |Cite
|
Sign up to set email alerts
|

Actitudes ante el Diagnóstico Enfermero: aplicación de la escala Position on Nursing Diagnosis en Canarias

Abstract: Introduction: nurses have different opinions and attitudes about the clinical functionality of Nursing Diagnosis.Objective: to describe the attitudes of Nursing professionals towards the Nursing Diagnosis.Method: observational, descriptive, cross-sectional study in a hospital in the Canary Islands (Spain). Position on Nursing Diagnosis is a validated instrument to measure the attitudes of nurses towards the Nursing Diagnosis with excellent reliability. It is made up by a coded scale of 20 pairs of opposite adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Kusumaningrum (2022) revealed that counseling could increase nurses' knowledge. Increased training and Nursing Diagnoses in the work environment show increased professional attitudes, especially acceptance, convenience, relevance, validity, creativity, and satisfaction (Rodríguez Suárez et al, 2022). Alhawri et al (2020) found a significant correlation between nurses' education and knowledge, attitude, and performance regarding nursing documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Kusumaningrum (2022) revealed that counseling could increase nurses' knowledge. Increased training and Nursing Diagnoses in the work environment show increased professional attitudes, especially acceptance, convenience, relevance, validity, creativity, and satisfaction (Rodríguez Suárez et al, 2022). Alhawri et al (2020) found a significant correlation between nurses' education and knowledge, attitude, and performance regarding nursing documentation.…”
Section: Discussionmentioning
confidence: 99%